CLIENT EXPERIENCE DAN PENGARUHNYA TERHADAP LOYALITAS PELANGGAN DENGAN CUSTOMER VALUE SEBAGAI VARIABEL MEDIASI PADA PT. KARTU NUSANTARA SEMESTA JAYAPURA - Zakaria; Yendra; Rasyid, Abdul; Tara, Halija (Journal of Economics Review (JOER), 2021)
This review plans to decide the impact of Customer Experience on Customer Loyalty through Customer Value at PT. Nusantara Card Semesta Jayapura. The populace in this review were 110 clients of PT. Nusantara Card Semesta Jayapura. Examining in this review utilizing purposive testing technique, with the models of clients situated in Jayapura City and its environmental factors, clients who have utilized the conveyance administration of PT. Nusantara Card Semesta somewhere twice, clients who send bundles through PT. Nusantara Card Semesta over the most recent 3 years. The examination information was acquired by dispersing polls straightforwardly to respondents which contained 11 explanations estimated utilizing a Likert scale. The information examination strategy in this review utilizes underlying condition demonstrating with the assistance of the Amos SEM application. The outcomes show that Customer Experience has a huge beneficial outcome on Customer Value, Customer Experience has a huge beneficial outcome on Customer Loyalty, Customer Value has a critical constructive outcome on Customer Loyalty, Customer Value intervenes the impact of Customer Experience on Customer Loyalty